Innate Immune Protection against Infectious Diseases by Pulmonary Administration of a Phospholipid-Conjugated TLR7 Ligand - Wu, Christina C.N. (S. Karger AG, 2014)
Pulmonary administration of Toll-like receptor (TLR) ligands protects hosts from inhaled pathogens. However, systemic side effects induced by TLR stimulation limit clinical development. Here, a small-molecule TLR7 ligand conjugated with phospholipid, 1V270 (also designated TMX201), was tested for innate immune activation and its ability to prevent pulmonary infection in mice. We hypothesized that phospholipid conjugation would increase internalization by immune cells and localize the compound in the lungs, thus avoiding side effects due to systemic cytokine release. Pulmonary 1V270 administration increased innate cytokines and chemokines in bronchial alveolar lavage fluids, but neither caused systemic induction of cytokines nor B cell proliferation in distant lymphoid organs. 1V270 activated pulmonary CD11c+ dendritic cells, which migrated to local lymph nodes. However, there was minimal cell infiltration into the pulmonary parenchyma. Prophylactic administration of 1V270 significantly protected mice from lethal infection with Bacillus anthracis, Venezuelan equine encephalitis virus and H1N1 influenza virus. The maximum tolerated dose of 1V270 by pulmonary administration was 75 times the effective therapeutic dose. Therefore, pulmonary 1V270 treatment can protect the host from different infectious agents by stimulating local innate immune responses while exhibiting an excellent safety profile.